2019
DOI: 10.1111/rsp3.12229
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion Policy and European identity building: Trust as a mediating element

Abstract: The understanding of the role of Cohesion Policy on the processes of European identity building is becoming more and more important in a period or resurgence of nationalisms and Euroscepticism. However, empirical evidence on this is still extremely scarce, due to both conceptual issues and data limitations. The present study tackles these limits and presents an empirical analysis of the way in which satisfaction with Cohesion Policy affected identification with Europe in EU regions between 2014 and 2017. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
1
11
1
Order By: Relevance
“…Second, our findings provide evidence of a positive association between Cohesion Policy attitudes and European identity. This contrasts with studies that have not found a positive and significant relationship between Cohesion Policy funding and European identity (Verhaegen et al, 2014;Capello and Perucca, 2019), but which have not investigated the role of well-known cognitive, instrumental and communicative drivers of identity through Cohesion Policy. We found that the perceived benefits of Cohesion Policy for citizens and for their region's development contribute to European identity.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Second, our findings provide evidence of a positive association between Cohesion Policy attitudes and European identity. This contrasts with studies that have not found a positive and significant relationship between Cohesion Policy funding and European identity (Verhaegen et al, 2014;Capello and Perucca, 2019), but which have not investigated the role of well-known cognitive, instrumental and communicative drivers of identity through Cohesion Policy. We found that the perceived benefits of Cohesion Policy for citizens and for their region's development contribute to European identity.…”
Section: Discussioncontrasting
confidence: 78%
“…Analysis of an original survey dataset of 8559 citizens in 17 EU regions provides empirical support for our theoretical expectations. In doing so, our findings challenge and refine the conclusions of studies that do not find an association between EU funding and European identity (Capello and Perucca, 2019;Verhaegen et al, 2014).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Capello and Perucca () focus on the association between support to the EU and European identity (link B in Figure ), studying the context conditions under which Cohesion Policy promotes identification, once accounted for the individuals' support to the EU institutions. Their results show that the gap in identification with Europe is highly dependent on the recent regional economic performance, supporting the idea that Cohesion Policy could have a significant impact on European identity if its goal of promoting economic convergence within the EU is achieved.…”
Section: Structure Of the Special Issuementioning
confidence: 99%
“…Taken together, the results from these studies support the general messages and policy implications discussed in the previous section. Cohesion Policy could be a powerful tool for promoting European identity, if the target of reduction of inequality within the EU is achieved (Aiello et al, ; Capello & Perucca, ; Dąbrowski et al, ). At the same time, however, this is likely to happen only if effective strategies of information, communication and involvement will be developed and implemented (Brasili et al, ; López‐Bazo & Royuela, ; Smętkowski & Dąbrowski, ).…”
Section: Structure Of the Special Issuementioning
confidence: 99%